Case report: Bullous pemphigoid in HIV-1-positive patients: interplay or coincidence? A case series and review of the literature - Foerster, Yannick; Sollfrank, Lukas; Rechtien, Laura; Harrer, Thomas; Berking, Carola; Sticherling, Michael (Frontiers in Immunology, 2023)
Bullous pemphigoid (BP) is an autoimmune inflammatory skin disease, mostly affecting the elderly population. Therefore, patients often have multiple comorbidities, but there is inconsistent data regarding the relationship between HIV-1 infection and BP, which has been rarely reported in combination. Herein, we describe three patients who presented with BP and concomitant HIV-1 infection that was well controlled with modern combined antiretroviral therapy. All patients received topical and oral corticosteroids. Depending on the individual severity, further add-on therapeutics, such as azathioprine, dapsone, doxycycline and the interleukin 4/13 antibody dupilumab, were added to the therapy regimen. All patients recovered from pruritic skin lesions and blistering. The cases are further discussed in the context of the current study landscape. In conclusion, HIV-1 infection shifts the cytokine profile from T-helper type 1 (TH1) towards T-helper type 2 (TH2), resulting in the excessive secretion of distinct cytokines, such as interleukin 4 (IL-4) and interleukin 10 (IL-10). With IL-4 being a main driver in the pathogenesis of BP, HIV-1-positive patients may benefit greatly from targeting IL-4 with monoclonal antibodies.